A Forming Poem': Towards a Process Poetics - Jones, Lacey (Literature and theology, 2019)
Even as theopoetics turns to literary structures and grammatology to arbitrate between an Absolute and Absolute meaninglessness, John Caputo and David Miller are careful to separate its project from theopoetry's representations of God. But this division makes little provision for figures like Denise Levertov, whose work suggests that the religious question is an inherently aesthetic one, that this arbitration can happen through representation. This article reads Levertov's The Tide' in order to define a mode of signification unbound to spiritual fixity. Through its characterisation of both form and faith as process, The Tide' offers a new way of negotiating the relationship between literature and theology.